Basic measurements of radiation at station Rock Springs (1998-06 et seq) - John Augustine; John Deluisi (PANGAEA, 2025)
This is a compilation of all short-wave and long-wave radiation datasets from Rock Springs that were and are published in the frame of BSRN. New data will be added regularly. The data are subject to the data release guidelines of BSRN (https://bsrn.awi.de/data/conditions-of-data-release/).